Effects of artificial light at night on the leaf functional traits of freshwater plants. (12th October 2021) - Segrestin, Jules; Mondy, Nathalie; Boisselet, Christelle; Guigard, Ludivine; Lengagne, Thierry; Poussineau, Sophie; Secondi, Jean; Puijalon, Sara
Abstract: The increasing use of artificial light at night has led to ecosystem exposure to light pollution worldwide. Aquatic ecosystems are particularly exposed, since lit road networks, urban development and industrial infrastructure are frequently located along river, lake, and sea shores. Although the negative effects of night‐time lighting on the physiology, behaviour, and life‐history traits of animals have been largely documented, there is a large knowledge gap about the responses of plants, especially regarding leaf functioning and resource‐management strategies. Some authors have proposed contrasting hypotheses of mechanistic responses to dim light at night in plants, but empirical results are still lacking. Based on field measurements of nocturnal irradiance in freshwater ecosystems located in peri‐urban areas, we performed a mesocosm experiment using three species of submerged aquatic plants. After 5 months of exposure to realistic dim light at night, four functional traits related to the resource management at the leaf level were measured. Artificial light at night had significant effects on the leaf physiology or chemistry, affecting their resource acquisition rate, but with different response intensities depending on the species. No effect was found on morphological or biomechanical traits for any of the studied species. These results support the hypothesis that plants could interpret dim light at night as a shaded environment and respond accordingly. We demonstrated that the effects of light at night on plants may have been underestimated in previous work. By modifying biotic interactions (e.g., competition and herbivory), these responses can have profound effects on community structure and ecosystem functioning.